Analysis of the antimicrobial activity of the essential oil of oregano (Origanum vulgare): a review study on the main effects on pathogens - Araújo, Daniel Lopes (2021)
Western medicine has been trying to use natural means for the treatment of infections caused by bacteria, in this context, it is very noticeable the great interest of therapeutic agents coming from natural products, more specifically those derived from plants. In this sense, a review of the integrative literature on the antimicrobial activity of the essential oil of oregano has been carried out. For this review of integrative literature 24 scientific articles were used. The studies showed that the essential oil of Origanum vulgare L. (Lamiaceae) has been used as an element of scientific research in laboratories as an antimicrobial strategy against innumerable types of bacteria, where its high therapeutic and antimicrobial content has been proven. The essential oil of O. vulgare exposes a variable range of active compounds, being the monoterpenes carvacrol and thymol the majority compounds of this essential oil, which corresponds between 80,2 and 98% of the total composition of this essential oil. In view of this, the results that were described in this review could suggest that the compounds cited have antimicrobial activity, damaging the lipidic plasma membranes, compromising the pH homeostasis and the balance of organic ions, preventing cell division and causing dehydration in bacterial cells.